Does Commitment to Celibacy Lead to Burnout or Enhance Engagement? A study among the Indian Catholic Clergy - Joseph, Eugene; Corveleyn, Joseph; Luyten, Patrick; De Witte, Hans (European Journal of Mental Health, 2010)
Burnout and engagement in general are thought to be associated mostly with work related factors and sometimes with personal factors as well. Over the past three decades a number of studies among clergy have identified various causes for priests’ susceptibility to burnout and have linked various independent variables in the study of burnout among clergy. However, a study on the association between commitment to celibacy, burnout and engagement among clergy has not been attempted. Is celibacy psychologically a possible way of life? In the Catholic Church (Latin Rite), the sacrament of Holy Orders for the presbyterate is normally conferred only on candidates who are ready to freely embrace and publicly manifest their intention of staying celibate for the love of God’s kingdom and the service of human beings. This study among Indian Catholic clergy contributes to the literature of burnout and engagement by studying the association of commitment towards priestly celibacy with clergy burnout and engagement – a new venture in the field of burnout and engagement. In addition, for the first time the construct of engagement has been used among clergy. Hierarchical regression analyses in the sample of 511 Catholic diocesan priests from South India confirmed that commitment to celibacy was negatively associated with burnout (that is it had a negative association with emotional exhaustion and depersonalisation and a positive association with personal accomplishment), and on the other hand, it was positively associated with engagement.